Global research hotspots and trends in the field of spine surgery during the COVID-19 pandemic: A bibliometric and visual analysis - Lin, Guang-Xun; Kotheeranurak, Vit; Chen, Chien-Min; Hu, Bao-Shan; Rui, Gang (Frontiers in Surgery, 2022)
Background: The Coronavirus disease-2019 (COVID-19) significantly affected the healthcare and research systems, including spine surgery, throughout the world. A bibliometric analysis allows graphical visualization of the development of an academic field and its frontiers. Since research concerning spine surgery during the COVID-19 pandemic is being constantly upgraded, we conducted a bibliometric analysis of this literature to investigate the current status, research hotspots, and trends in this field. Methods: We searched the Web of Science database for literature published (from December 1, 2019, to March 24, 2022) using the terms “COVID-19” OR “2019-nCoV” OR “SARS-CoV-2” AND “spine surgery” OR “spinal surgery” OR “discectomy” OR “decompression” OR “laminectomy” OR “interbody fusion” OR “pedicle screws.” Detailed bibliometric and visual analysis of the number of publications, geographical distribution, institutions, journals, authors, and keywords was done using CiteSpace, VOSviewer, and R-Bibliometrix. Results: Of the initially screened 173 articles, we included 84 relevant articles – 62 original articles, 10 editorial materials, 8 reviews, and 4 others. The United States, China, Egypt, and Argentina were most actively publishing in the field of spine surgery and COVID-19. The AOSpine International community contributed 7 articles (24 citations). The Hospital for Special Surgery (13.1%) and Johns Hopkins University (13.1%) were institutions with the most publications. Using the Law of Bradford, we found that World Neurosurgery, Global Spine Journal, and European Spine Journal are the core journals in this field, with P. K. Louie being the most influential author. “Elective surgery,” “intensive care,” “telehealth,” “patient satisfaction,” and “follow-up” had the strongest citation bursts. Conclusions: During the COVID-19 pandemic, spine surgeons were more concerned with surgical timing, care, treatment, and patient's quality of life. Accordingly, research hotspots in spine surgery during the pandemic shifted from “early healthcare” to “virus management” and “experience and education.”